MANAGERIAL SKILLS AND SMALL AND MEDIUM SCALE ENTERPRISES GROWTH: A CONCEPTUAL REVIEW - Christian, Iheanacho; Isyaka, Mohammed Salisu; NaiAllah, Shehu Rabiah (Kashere Journal of Management Sciences, 2024)
This study assessed the effect of managerial skills on the growth of Small and Medium Enterprises (SMEs) in Nigeria, recognizing their crucial role in the nation’s economic transformation from an agrarian to a service-centered economy. Managerial skills, encompassing technical, human, and conceptual skills, are vital for entrepreneurs navigating the complexities of business growth. The research adopted Robert L. Katz’s Managerial Skills Theory and utilized a systematic literature review approach. Data synthesis involved categorizing findings based on types of managerial skills and their impact on SME performance metrics such as productivity, innovation, and profitability. The study revealed a significant geographical bias, with most research focusing on urban centers and neglecting the unique challenges faced by rural SMEs, including limited access to resources and infrastructure. Additionally, there was a notable gap in understanding the integration of managerial skills with other critical growth factors like financial resources, market conditions, and regulatory environments. The study recommended conducting research focused on rural SMEs to address their specific challenges and exploring the interplay between managerial skills and other growth determinants. These recommendations aim to provide a comprehensive understanding of SME growth dynamics and develop integrated strategies that SMEs can implement effectively.